2016
DOI: 10.1016/j.ebiom.2016.04.039
|View full text |Cite
|
Sign up to set email alerts
|

LEDGIN-mediated Inhibition of Integrase–LEDGF/p75 Interaction Reduces Reactivation of Residual Latent HIV

Abstract: Persistence of latent, replication-competent Human Immunodeficiency Virus type 1 (HIV-1) provirus is the main impediment towards a cure for HIV/AIDS (Acquired Immune Deficiency Syndrome). Therefore, different therapeutic strategies to eliminate the viral reservoirs are currently being explored. We here propose a novel strategy to reduce the replicating HIV reservoir during primary HIV infection by means of drug-induced retargeting of HIV integration. A novel class of integration inhibitors, referred to as LEDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
140
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(169 citation statements)
references
References 81 publications
28
140
1
Order By: Relevance
“…Second, since integrase is produced by protease-mediated cleavage of the Pr160 Gag-Pol precursor protein, PIs might inhibit HIV-1 integration by preventing the formation of a functional integrase19. Impaired integrase activity and/or impairment of the integrase-LEDGF/p75 interaction could result in a decreased number of integrated provirus in transcriptionally active sites, but also could favor the viral integration in less transcriptionally active sites which will result in lower viral reactivation22. Third, HIV PIs have been reported to block Akt activation23, and we recently observed that PIs, by blocking Akt activation especially triggered by Nef, limit HIV-1 recovery from latently-infected T cells24.…”
Section: Discussionmentioning
confidence: 99%
“…Second, since integrase is produced by protease-mediated cleavage of the Pr160 Gag-Pol precursor protein, PIs might inhibit HIV-1 integration by preventing the formation of a functional integrase19. Impaired integrase activity and/or impairment of the integrase-LEDGF/p75 interaction could result in a decreased number of integrated provirus in transcriptionally active sites, but also could favor the viral integration in less transcriptionally active sites which will result in lower viral reactivation22. Third, HIV PIs have been reported to block Akt activation23, and we recently observed that PIs, by blocking Akt activation especially triggered by Nef, limit HIV-1 recovery from latently-infected T cells24.…”
Section: Discussionmentioning
confidence: 99%
“…Vranckx et al have shown that LEDGF/p75 depletion hampers HIV-1 reactivation in cell culture, and they demonstrated that LEDGINs relocate and retarget HIV integration, resulting in a HIV reservoir that is refractory to reactivation by different latency-reversing agents (20).…”
Section: Introductionmentioning
confidence: 99%
“…Initially designed to prevent the IN-LEDGF/p75 interaction, it was later evidenced that these molecules have an additional biochemical activity based on the induction of allosteric conformational changes of IN that ultimately trigger its aberrant multimerization (10)(11)(12)(15)(16)(17)(18)(19). This effect is independent of the presence of LEDGF/p75 and the viral DNA and results from the binding of the inhibitors to the IN dimer interface that is also part of the LEDGF-binding pocket.Given their dual biochemical activities, INLAIs were shown to block HIV-1 replication at two different steps: the inhibition of IN-LEDGF/p75 binding accounts for an "early" block at integration, while INLAI-promoted IN multimerization results in a "late" effect during virus maturation (11,12,17,18).Vranckx et al have shown that LEDGF/p75 depletion hampers HIV-1 reactivation in cell culture, and they demonstrated that LEDGINs relocate and retarget HIV integration, resulting in a HIV reservoir that is refractory to reactivation by different latency-reversing agents (20).HIV-1 virions produced in the presence of INLAIs are non-infectious because they are unable to complete reverse transcription upon target cell infection (12,17,18). Investigating the molecular bases of the observed infectivity defects, we found that HIV-1 virions produced in the presence of the quinoline INLAI compound BI-D (developed by Boehringer Ingelheim) package normal levels of genomic RNA dimer and harbor a properly placed tRNA lys3 primer that could be extended ex vivo.…”
mentioning
confidence: 99%
“…In addition to decreasing integration levels, the R263K substitution may also alter integration sites. Changes in integration sites were observed when infections are performed in the presence of suboptimal concentrations of RAL or noncatalytic integrase inhibitors but also with the D116N catalytically inactive integrase mutant (2729). In the case of the R263K substitution, however, these changes are unlikely to alter the establishment of or reactivation from latency, since we previously reported these processes to be unaffected by this substitution (30).…”
Section: Discussionmentioning
confidence: 99%